(3eOjQ GdeOQSI eOjQ GdhbJ CjVkG (B... : (3OhQ eOjQ GdeOQSI GdQSejI aj EOGQI GdhbJ ajgGs - (3HGTG, SMQ Ydjs ((3HjQhJs (3GdLGeYI GdGSdGejI (B- (3cdjI GdCOGH hGdYdhe GdGfSGfjIs, 2014)
(3JgOa GdOQGSI Edi eSGYOI GdeOjQjf aj EOQGc CgejI EOGQI GdhbJ aj GdeOQSI Ydi cd GdeSJhjGJ GdYedjI hJbOje GdebJQMGJ GdeajOI aj Pdc(B. (3EVGaI Edi JMOjO CHQR GdeeGQSGJ GdeNdI HEOGQI GdhbJ dOi eOjQj GdeOGQS heSGYOI eUeej HQGeL JOQjH GdeOjQjf aj eQGcR GdJOQjH GdJQHhj Ydi GdYfGjI HYfUQ GdhbJ hEjdGFg GdCgejI GdefGSHI aj HQGeLge GdJOQjHjI, HGdTcd GdPj jSge aj QaY caGAI eOjQj GdeOGQS hJfejI bOQGJge Ydi GdJNWjW GdLjO ddhbJ(B. (3hJgOa GdOQGSI CjVkG Edi GbJQGM HQfGeL CSHhYj ddeOjQ jSGYOg HJfXje egGeg hJfajPgG, hMK Gdbjejf Ydi GdeOGQS GdQSejI Ydi GdGdJaGJ dgPg GdeTcdI hGdSYj dEjLGO GdMdhd GdefGSHI dgG(B. (3hbO TedJ GdYjfI eOGQS aj GdJYdje GdCSGSj GdQSej aj SGMd GdeJf GdLfhHj(B. (3HjfJ GdOQGSI (B1) (3hLhO aQhb Hjf eOjQj GdeOGQS aj eLGd EOGQI GdhbJ JYRi deJZjQ GdLfS, hcPdc aj eLGd QYGjI TDhf GdYGedjf(B. 2) (3ZjGH GdOhQGJ GdJOQjHjI GdYedjI GdeJNUUI aj EOGQI GdhbJ deOjQj GdeOGQS(B. 3) (3YOe JMOjO ehGYjO eMOOI dRjGQI ChdjGA GdCehQ ddeOQSI(B. 4) (3ZjGH GdNWI GdeOQSjI hGdUjGfI GdSQjYI ddCLgRI aj GdeOQSI(B. 5) (3YOe JMOjO eOI GdELJeGYGJ(B.s
(3GdfhY (B: (3QSGdIs
Keywords: (3GdGOGQI GdeOQSjIs; Gestion scolaire; Public Sector; School management; Secteur Public; (3GdJYdje GdQSejs